Uguaglianza nella diversità. Identità religiose e democrazia costituzionale (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Introduzione - 2. Disegno costituzionale e rigidità politico-normative: quale strada per una equilibrata disciplina del fenomeno religioso? - 3. Conclusioni.Equality in diversity. Religious identities and constitutional democracyABSTRACT: The entry into force of the new system after the fall of fascism did not constitute the resolutive element to mark a decisive turning point in the Italian ecclesiastical politics, with the implementation of a system of reforms in religious matters consistent with the innovative will of the institutional change that occurred in the Country. The consequence is that, seventy years after the adoption of the Republican Constitutional Charter, many normative provisions still conform to the inspiring principles of the fascist system, and there are many impediments to the concrete realization of the principles of freedom and democracy, with serious damage for the enjoyment of constitutional guarantees by spiritual minorities. With the approval of a general legislation on religious interests, the equal enjoyment of the fundamental rights could be achieved, both for individuals and for groups, within a framework of definitive overcoming of the fascist penalizing legislation and of fixation of the regulatory law criteria of the various treatments to protect spiritual specificities.